Corporate social responsibility management based on Maqashid Al- Shariah - Fatin Fadhilah Hasib, A Syifaul Qulub, Ririn Tri Ratnasari, (Opción, 2019)
This research aims to describe Shariah-based corporate social responsibility management in accordance with Maqashid Al-Shariah principles as a new perspective on PT Petrokimia Gresik via qualitative and phenomenological approach with two modes as recommended by Bogdan and Biklen as an analysis technique. This study result showed that programs carried out by PT Petrokimia Gresik are in tune with Maqashid Al-Shariah. In conclusion, BUMN management, especially PT Petrokimia Gresik is expected to be able to carry out CSR management that provides great benefits to the community with programs that are innovative and have a good impact on the company’s future